Pengaruh lingkungan kerja non fisik dan kepemimpinan terhadap produktivitas kerja pemanen pada PT. Sekarbumi Alamlestari di Tapung Hilir - Hendria, Devi; Hendriani, Susi; Hamid, Liswar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The study was conducted at PT. Sekarbumi Alamlestari in the Desa Kota Garo, Tapung Hilir, Kampar, province of Riau which began in November 2012 to August 2013, with the aim of analyzing the Non-Physical Effects of Work Environment and Leadership to Work Productivity of Harvesters at PT. Sekarbumi Alamlestari In Tapung Hilir. In this study consisted of three variables: the dependent variable and two independent variables . The sample in this study as many as 71 people, the determination of the number of samples based on the method Slovin. While the data analysis using quantitative methods is the method of doubled linear equations with the help of the SPSS ( Statistical Package for Social Science ) version 17.0. Based on the results of analysis show that the non-physical work environment and leadership have a significant effect on the productivity of the harvester at PT. Sekarbumi Alamlestari in Tapung Hilir. While the variables that have the most dominant effect on employee productivity at PT. Sekarbumi Alamlestari in Tapunh Hilir is the work environment variable. Thus it can be interpreted that the non-physical work environment and leadership have significant and positive effect on employee productivity at PT. Sekarbumi Alamlestari in Tapung Hilir.Based on the study results, the authors suggest that the management of PT. Sekarbumi Alamlestari in Tapung Hilir further improve the quality of leadership by putting a person based on their ability so they can create the right ideas in every activity of target achievement without anyone feeling undifferentiated. Thus it will create a comfortable working environment for all elements of the company.Keywords: Productivity, Non Physical Work Environment, Leadership